Analysis, modelling and design considerations for the excitation systems of synchronous generators - Nuzzo, Stefano; Galea, Michael; Gerada, C.; Brown, Neil (Institute of Electrical and Electronics Engineers, 2017)
The traditional generating set is usually comprised of a classical, wound-field, salient-pole or cylindrical rotor synchronous generator, excited by a separate smaller machine, via a rotating, uncontrolled diode rectifier. The effects of the commutation processes of the diode bridge are often overlooked and neglected. However due to the uncontrolled nature of this process, the rectified voltage available at the main generator’s rotor terminals can be significantly lower than the expected value. This is especially true for low-to-medium power rated systems. In this paper, a detailed investigation of these aspects is done and an accurate voltage drop prediction model is then proposed. The model is validated with finite element analysis and with experimental results for a particular low-medium rated generating system in the 400kVA power range. The validated tool is then integrated into an innovative design tool, which first performs an analytical pre-sizing procedure and then utilizes a genetic algorithm approach to identify an optimal excitation system design, aimed at minimizing the voltage drop ensuing from the diode commutations, with minimum impact on the overall efficiency.